Survei Aktivitas Fisik SMP N 1 Borobudur Kabupaten Magelang Di Masa Pandemi Covid - 19 Tahun 2020 (Universitas Negeri Semarang, 2021)
ABSTRACT Paraditya Garin Akhbar Syah. 2020. â€œSurvey of Physical Activity of Students of SMP Negeri 1 Borobudur, Magelang Regency during the Covid - 19 Pandemic, 2020â€. â€. A thesis. Department of Physical Education, Health and Recreation. Faculty of Sport Sciences. Universitas Negeri Semarang. Advisor: Dr Mugiyo Hartono, M.Pd Kata Kunci: Physical Activity, Junior High School Students, Covid-19 pandemic The problem of this research is how the physical activities carried out by students of SMP Negeri 1 Borobudur at home during the Covid-19 pandemic? This research uses survey research and data collection techniques using a questionnaire. Involving the student population of SMP Negeri 1 Borobudur, Magelang Regency. This research used a sample of 144 students who were taken randomly (random sampling) from each class with physical activity while at home. The method of analysis in this research is descriptive quantitative research. The result of this research is the data analysis technique used was descriptive analysis with a significant level of 5%.the results of descriptive statistical analysis for the physical activity variables of the students of SMP N 1 BOROBUDUR during the Covid-19 epidemic as a whole obtained the maximum value = 0.00, minimum value = 4.08, average (mean) = 2.19, median = 2 , 03, the mode of = 1.75; standard deviation = 0.75.It is known that the physical activity of SMP N 1 Borobudur students during the Covid-19 epidemic was in the low category as much as 45.13%, the moderate category was 36.11%, the high category was 15.97%, the very low category was 2.08% and in the very high category 0.69%, the conclusion in this study is that the physical activity of the students of SMP N 1 Borobudur during the Covid-19 epidemic was low. Students are expected to continue doing activities or exercising at home regularly to maintain their health during the Covid - 19 pandemic.